Ractopamine hydrochloride on performance and carcass traits of confined Nellores cattle - João Luis Kill; Ismail Ramalho Haddade; Iron Cardoso dos Santos Júnior; Douglas Haese; Alberto Chambela Neto; Pedro Veiga Rodrigues Paulino; Carolina D'ávila Possatti (Ciência Rural, 2015)
The effect of four levels of inclusion (0; 450; 900 and 1,350g T-1) of Ractopamine hydrochloride was assessed concerning weight gain, feed conversion, dry matter intake, carcass traits and quality of castrated male cattle meat in confinement. Forty Nellore steers were used, with an average age of 26 months and initial average weight of 423.4±2.7kg, in a randomized block experimental design with four treatments and ten replications. The diet was fixed with the ratio of forage to concentrate dry matter of 75.3:24.7. A Linear positive effect observed was the inclusion of Ractopamine on daily weight gain and linear negative effect on feed conversion, highlighting the improvements with the increasing inclusion of Ractopamine hydrochloride. In relation to carcass traits, the linear effect was negative for fat thickness and no differences were found regarding the hot carcass weight ; carcass yield; area, width and depth of rib eye area of the Longissimus dorsi muscle, and noble courts. In relation to dry matter intake, the comparison of the treatments demonstrated that Ractopamine didn't influence negatively, which highlights its positive effect on the animal performance. The use of Ractopamine improves performance and decreases de amount of superficial fat in male nellore carcass in confinement.